2018
DOI: 10.3389/fphar.2018.00605
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Activates Autophagy via Down-Regulation of the NF-κB Signaling-Mediated Apoptosis in Chondrocytes

Abstract: Osteoarthritis (OA) is a common chronic and degenerative joint condition that is mainly characterized by cartilage degradation, osteophyte formation, and joint stiffness. The NF-κB signaling pathway in inflammation, autophagy, and apoptosis plays a prominent role in the progression of OA. Icariin, a prenylated flavonol glycoside extracted from Epimedium, have been proven to exert anti-osteoporotic and anti-inflammatory effects in OA. However, the action mechanisms of its effect on chondrocytes have yet to be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 55 publications
2
56
1
Order By: Relevance
“…In addition, Li X et al reported that the ERK1/2 signaling pathways activation was involved in chondrocyte autophagy, which protected chondrocyte from apoptosis [41]. Moreover, Pathways such as AMPK/mTOR [42], PI3K/AKT [43], and AKT/mTOR [39] were associated with autophagy in chondrocytes. We found that ASP -induced autophagy plays a critical role in the prevention of SNPinduced apoptosis via the ERK1/2 signaling pathway (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Li X et al reported that the ERK1/2 signaling pathways activation was involved in chondrocyte autophagy, which protected chondrocyte from apoptosis [41]. Moreover, Pathways such as AMPK/mTOR [42], PI3K/AKT [43], and AKT/mTOR [39] were associated with autophagy in chondrocytes. We found that ASP -induced autophagy plays a critical role in the prevention of SNPinduced apoptosis via the ERK1/2 signaling pathway (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is regulated by multiple signaling pathways in chondrocytes. Inhibition of NF-κB pathway promotes the expression of Atg5, Atg7, and LC3II, and activates autophagy [39]. Shi et al showed that autophagy levels were signi cantly inhibited after activation of the p38 signaling pathway in osteoarthritis [40].…”
Section: Discussionmentioning
confidence: 99%
“…ICA, the extract of Epimedium, is known to have anti-oxidative, anti-neuroinflammatory, and anti-apoptotic effects and considered to be effective for a range of disorders, such as neoplasm, Alzheimer's disease, cerebral ischemia, depression, diabetes, and Parkinson's disease (PD) [22][23][24][25]. For OA, ICA was identified as an anti-osteoporotic and anti-inflammatory compound through multi-target mechanisms, including the suppression of NF-κB signaling and inhibition of MMP1, MMP3, and MMP13 expression or OPG-RANKL-RANK system via MAPK pathways [13][14][15]. The present study demonstrated that ICA inhibited LPS-mediated chondrocytes injury and pyroptosis and alleviated rat osteoarthritis by inhibiting NLRP3 and caspase-1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Icariin (ICA) which is the extract of Epimedium was identified as the effective constituent, showing anti-osteoporotic and anti-inflammatory effects [12]. Studies revealed that ICA prevented OA inflammation and chondrocytes apoptosis though activation of autophagy via inhibiting NF-κB signaling pathway [13]. Furthermore, ICA exerted a chondroprotective effect through the inhibition of MMP-1, MMP-3, and MMP-13 or the suppression of osteoprotegerin (OPG), receptor activator of nuclear factor kappa-B ligand (RANKL), and receptor activator of nuclear factor kappa-B (RANK) system via MAPK pathway in IL-1β-stimulated chondrosarcoma cells [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In cancer cells, icariin displays anticancer activity by significantly promoting apoptosis [25,26]. In contrast, icariin protects normal cells against cell apoptosis induced by various stimuli, including HG [27,28]. More studies are necessary to elucidate the mechanism underlying this discrepancy.…”
Section: Discussionmentioning
confidence: 99%